Book clubs : women and the uses of reading in everyday life - Long, Elizabeth (Chicago : University of Chicago Press, 2003)
Book clubs are everywhere these days. And women talk about the clubs they belong to with surprising emotion. But why are the clubs so important to them? And what do the women discuss when they meet? To answer questions like these, Elizabeth Long spent years observing and participating in women's book clubs and interviewing members from different discussion groups. Far from being an isolated activity, she finds reading for club members to be an active and social pursuit, a crucial way for women to reflect creatively on the meaning of their lives and their place in the social order.
On the social nature of reading -- Nineteenth-century white women's reading groups : literary inspiration and social reform -- Between past and present : introductory reflections on the changing nature of women's reading groups -- Exploring the social world of Houston's reading groups -- Book selection : negotiating group identity through literature -- Conversing with books, fashioning subjectivity, dealing with difference -- Reading groups and the challenge of mass communication and marketing -- At the end
Str. 235-245: Bibliografija
Kazalo
Keywords: klubovi knjige - SAD - analiza (opis) pojedinih slučajeva; žene - knjige i čitanje - SAD - analiza (opis) pojedinih slučajeva; čitanje - društveni aspekti - SAD - analiza (opis) pojedinih slučajeva